Concept Lattices and Their Applications Fourth International Conference, CLA 2006 Tunis, Tunisia, October 30-November 1, 2006 Selected Papers - Yahia, Sadok Ben.; Nguifo, Engelbert Mephu; Belohlavek, Radim; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
This book constitutes the refereed proceedings of the Fourth International Conference on Concept Lattices and their Applications, CLA 2006, held in Tunis, Tunisia, October 30-November 1, 2006. The 18 revised full papers together with 3 invited contributions presented were carefully reviewed and selected from 41 submissions. The topics include formal concept analysis, foundations of FCA, mathematical structures related to FCA, relationship of FCA to other methods of data analysis, visualization of data in FCA, and applications of FCA.
Invited Contributions -- An Intelligent User Interface for Browsing and Searching MPEG-7 Images Using Concept Lattices -- First Elements on Knowledge Discovery Guided by Domain Knowledge (KDDK) -- Formal Concept Analysis as Applied Lattice Theory -- Foundations -- Direct Factorization by Similarity of Fuzzy Concept Lattices by Factorization of Input Data -- Succinct System of Minimal Generators: A Thorough Study, Limitations and New Definitions -- Closure Systems of Equivalence Relations and Their Labeled Class Geometries -- Generalizations of Approximable Concept Lattice -- Methods -- Rule Validation of a Meta-classifier Through a Galois (Concept) Lattice and Complementary Means -- Graded LinClosure and Its Role in Relational Data Analysis -- Yet Another Approach for Completing Missing Values -- Efficient Generic Association Rules Based Classifier Approach -- Galois Lattices and Bases for MGK-Valid Association Rules -- Generic Association Rule Bases: Are They so Succinct? -- Concept Lattice Representations of Annotated Taxonomies -- An Algorithm to Find Frequent Concepts of a Formal Context with Taxonomy -- Applications -- Unique Factorization Theorem and Formal Concept Analysis -- Towards Concise Representation for Taxonomies of Epistemic Communities -- Towards an Iterative Classification Based on Concept Lattice -- Using Formal Concept Analysis for Mining and Interpreting Patient Flows within a Healthcare Network -- Using FCA to Suggest Refactorings to Correct Design Defects -- Type Signature Induction with FCAType.
Keywords: Mathematics; Data structures (Computer science).; Data mining; Information storage and retrieval; Artificial intelligence; Mathematical logic; Mathematics; Mathematical Logic and Foundations; Data Mining and Knowledge Discovery; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Data Structures; Data Storage Representation; Electronic books